PENGEMBANGAN FLASHCARD “SPOKEN” UNTUK MENINGKATKAN KETERAMPILAN MENULIS KALIMAT AKTIF SISWA KELAS II SEKOLAH DASAR - Agwianndini, Grace; Septian Airlanda, Gamaliel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The habit of communicating with English in daily life causes a decrease in students' ability to speak Indonesian. This research aims to develop Flashcard "SPOKEN" can improve the ability to write active sentences in grade 2 students in learning Indonesian at SD Karunia Global School Jambi. The method used in this study is Research and Development (RnD) which is adapted from Sukmadinata with the ADDIE (Analysis, Design, Develop, Implement & Evaluate) research and development model. Flashcard "SPOKEN" is used in Indonesian for grade 2 in active sentence material. The design uses cards containing words equipped with elegance and images. Flashcards contain sentence elements, namely Subject, Predicate, Object, and Description (SPOK). A validation score of 93% was obtained from media experts with the category of "Very Valid". From material experts, a validation score of 80% was obtained with the criteria of "Valid". Meanwhile, for linguists, a validation score of 80% was obtained with the criterion of "Valid". From the results of this percentage, the flashcard learning media "SPOKEN" can be declared feasible to be tested on a limited basis. The results of the questionnaire obtained from student responses averaged 91% with the category "Very Interesting". Meanwhile, the results of the teacher response questionnaire received a percentage of 100% with the category "Very Valid". The average score obtained by students was 64.18 and the posttest score obtained was 85.39. The results of the T Test showed that the significance value (Sig) of the measurement data was 0.000 < 0.05.